Effect of dietary supplementation of phytogenic feed additive on performance traits, serum neopterin, and cutaneous basophil hypersensitivity response in heat-induced stress model of broiler chickens - Marimuthu, Saravanakumar; Selvam, Ramasamy; Kaninathan, Arigesavan; D’Souza, Prashanth (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The trial was aimed at assessing the effect of phytogenic feed additive (PFA), a natural adaptogen, on growth performance, serum neopterin level, and cutaneous basophil hypersensitivity (CBH) response in heat-induced stress model of broilers. Materials and Methods: One-day-old Ross 308 chicks (N = 360) were randomly distributed among normal control (NOR), heat-stress control (HSC), and PFA treatment (HSC plus PFA at 200 gm/ton of feed) group. HSC and PFA groups were subjected to heat stress (HS) (32°C–36°C) from 9:00 a.m. to 5:00 p.m. for 35 days. The impact of HS on growth performance, serum neopterin level, and CBH response was assessed. Results: High ambient temperature worsened the performance traits [bodyweight (p < 0.05) and feed conversion ratio] and significantly lowered the serum neopterin level and CBH response in the HSC group when compared to the NOR group. However, supplementation of PFA at 200 gm/ ton of feed to birds mitigated the detrimental effects of HS. Conclusion: PFA at 200 gm/ton demonstrated the immunomodulatory effect through the restoration of serum neopterin level, CBH response, and growth performance traits in heat-stressed broiler chickens. Thus, PFA can be used as a natural adaptogen to increase the stress resistance and mitigate the negative consequences of various stressors in broiler chickens. J. Adv. Vet. Anim. Res., 7(1): 141-147, March 2020